Tanggapan Pemelajar Asing Tingkat Mahir dalam Pembelajaran Bahasa Indonesia terhadap Bahan Ajar Berbasis Web dengan Materi Cerita Pendek - Masduki Zakaria; Sumiyadi; Vismaia Damaianti (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The education, science, and technology continues to develop, no exception with BIPA learning. BIPA is foreign students in Indonesian language. This requires an innovation in learning short story texts for advanced BIPA students. This study describes the responses of advanced BIPA students to the use of web-based short story teaching materials that can be accessed through the page of bipaberkisah.com. This method used in this study is the Research and Development (R&D) method using the DDD-E (Decide, Design, Develop, Evaluate) model related to the evaluation or response stage from the user's point of view, namely advanced level BIPA students. The subjects of this research are BIPA students level proficient in one of the universities in Indonesia. Data collection is conducted from questionnaire with use scale Likert 1-5 and calculated by quantitative as well as explained more carry on use method descriptive. The results of the analysis show that the students' responses against theory web-based short stories are generally good. The results also indicate that the procurement of narrative text teaching materials, especially website-based short stories, can be an alternative innovative learning media that students can use.